Investigating the factors that influence the quality of open source systems - Awang Abu Bakar, Normi Sham; Arsat, Nadiah (2014)
Open Source Software (OSS) has impacted software industry and recently became extremely popular. Many agencies, especially the Malaysian government agencies are capitalizing on open source projects due to the merit it offers. Due to the vast usage in the industry and government administrations, there is a colossal need to investigate on the quality of applications. Therefore, this research will study the quality factors of OSS used by Malaysian government, namely MyMeeting, and MyTaskManager. In this research, McCall’s Quality Factor Model is used as a quality model and it emphasizes on quality factors such as maintainability, correctness, reliability, efficiency and usability. This research utilizes six object-oriented metrics by Chidamber and Kemerer (CK) to measure the quality factors of OSS. The metrics were analyzed using Statistical Package for Social Sciences (SPSS). Results from the data analysis show that coupling and complexity influence the class size.